Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00414-003-0407-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA D-loop hypervariable regions: Czech population data

Abstract: In order to identify polymorphic sites and to find out their frequencies and the frequency of haplotypes, the complete D-loop of mitochondrial DNA (mtDNA) from 93 unrelated Czech Caucasians was sequenced. Sequence comparison showed that 85 haplotypes were found and of these 78 were unique, 6 were observed twice and 1 was observed three times. Genetic diversity (GD) was estimated at 0.999 and the probability of two randomly selected sequences matching (random match probability, RMP) at 1.2%. Additionally these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
6
23
0
4
Order By: Relevance
“…This and a similar haplotype, lacking only the 16271 transition, are very rare in European Roma populations, being found only in the Spanish, Bulgarian and Hungarian Roma Egyed et al 2007). Among Europeans, such haplotypes have been revealed only in French (0.5%; Dubut et al 2004), Hungarian (0.5%; Egyed et al 2007) and Czech (about 3%; Vanecek et al 2004;Malyarchuk et al 2006b) populations. In the present study, we have found that 2.9% of individuals from eastern Slovakia are characterized by exactly the same J1 * -haplotype.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…This and a similar haplotype, lacking only the 16271 transition, are very rare in European Roma populations, being found only in the Spanish, Bulgarian and Hungarian Roma Egyed et al 2007). Among Europeans, such haplotypes have been revealed only in French (0.5%; Dubut et al 2004), Hungarian (0.5%; Egyed et al 2007) and Czech (about 3%; Vanecek et al 2004;Malyarchuk et al 2006b) populations. In the present study, we have found that 2.9% of individuals from eastern Slovakia are characterized by exactly the same J1 * -haplotype.…”
Section: Resultsmentioning
confidence: 49%
“…All available published data on HVS I mtDNA variability or RFLPs in Slavonic-speaking populations were used for comparative purposes: Bulgarians (Calafell et al 1996;Richards et al 2000), Russians (Malyarchuk et al 1995;Orekhov et al 1999;Richards et al 2000;Malyarchuk et al 2002;Belyaeva et al 2003;Malyarchuk et al 2004); Ukrainians (Malyarchuk & Derenko, 2001), Belorussians (Belyaeva et al 2003), Poles (Richards et al 2000;Malyarchuk et al 2002), Czechs (Richards et al 2000;Vanecek et al 2004;Malyarchuk et al 2006b), Bosnians (Malyarchuk et al 2003;Cvjetan et al 2004), Slovenians (Malyarchuk et al 2003;Zupanic Pajnic et al 2004), Croatians (Tolk et al 2000;Cvjetan et al 2004), Serbians, Herzegovinians and Macedonians (Cvjetan et al 2004).…”
Section: Phylogenetic and Statistical Analysismentioning
confidence: 99%
“…Therefore, the high mutational frequency in the D-loop region may not lead to the specific changes in tumors. The D-loop is the site that the mtDNA is nearest to the mitochondrial inner membrane and thus is most susceptible to the damage of ROS (24)(25)(26).…”
Section: Mtdna Mutations In Human Tumor Cellsmentioning
confidence: 99%
“…Position 527 is, for example, suspicious in the Czech population data from [72]: sample no. 64 is recorded with a deletion at this position, which seems to be implausiblealthough understandable, given the signals one typically observes at this position.…”
Section: Phantom Mutations In Hvs-iiimentioning
confidence: 99%